Does concern regarding climate change impact subsequent mental health? A longitudinal analysis using data from the Avon Longitudinal Study of Parents and Children (ALSPAC) - Daniel Major-Smith; Isaac Halstead; Katie Major-Smith (Royal Society Open Science)
Climate change is having a substantial—and increasingly severe—impact on our planet, affecting people’s health, security and livelihoods. As a consequence, the concept of ‘climate anxiety’ has recently been developed to characterize the psychological and emotional impact of concern over climate change. However, whether climate anxiety—or less extreme manifestations such as climate concern—impacts subsequent mental health is uncertain. Numerous studies have identified an association between climate anxiety and worse mental health, but as most of this research is cross-sectional it is impossible to infer the direction of causation (e.g. does climate anxiety cause broader mental health, or do broader mental health problems cause climate anxiety, or is there bidirectional causation?). In this paper, we used longitudinal data from young adults (aged approx. 30 years old) in the Avon Longitudinal Study of Parents and Children (ALSPAC) based in the UK. We first aimed to answer the following research question: does concern regarding climate change cause subsequent mental health? Our outcomes were a range of validated mental health scales for depression, anxiety and well-being, and analyses adjusted for a range of baseline confounders and prior mental health to try and estimate an unbiased causal effect. As a second research question, we explored whether the association between climate concern and mental health is moderated by whether participants engage in climate action and whether they believe that individual actions can mitigate the impacts of climate change. We found little evidence for a causal effect of climate concern on subsequent mental health or well-being, or for moderation of this relationship by these climate change beliefs and behaviours. Our results suggest that—in this population of young adults in the UK, at least—concerns regarding climate change do not, on average, appear to cause subsequent mental health issues. However, we stress that these results apply only to climate concern, and may not be generalizable to more extreme manifestations of climate anxiety.